Precision medicine in colorectal cancer: the molecular profile alters treatment strategies. (September 2015) - Tran, Nguyen H.; Cavalcante, Ludmila L.; Lubner, Sam J.; Mulkerin, Daniel L.; LoConte, Noelle K.; Clipson, Linda; Matkowskyj, Kristina A.; Deming, Dustin A.
When considering treatment options for patients with metastatic colorectal cancer (mCRC), molecular profiling has become a pivotal component in guiding clinical decisions. FOLFOX and FOLFIRI (fluorouracuil, leucovorin plus oxaliplatin or ininotecan, respectively) are the standard base regimens used for the treatment of mCRC. Biologic agents, such as the epidermal growth factor receptor (EGFR) targeted therapies, cetuximab and panitumumab and the vascular endothelial growth factor monoclonal antibody, bevacizumab, are safe and effective in the first-line setting. The most efficacious use of these agents in terms of timing and selection of the right patient population continues to be debated. Here we review multiple investigations into the effectiveness of treatment options as a function of the mutations present in colon cancers. Early studies have reported that KRAS mutations at exon 2 predict resistance to EGFR targeted therapies. More recently the data have expanded to include KRAS mutations at exons 3 and 4 and NRAS mutations at exons 2, 3 and 4 as well as other biomarkers including BRAF and PIK3CA, leading to the evolution of the treatment of mCRC to a more precision-based approach. As our understanding of relevant biomarkers increases, and data from both molecular profiling and treatment response become more readily available, treatment options will become more precise and their outcomes more effective.